2003
DOI: 10.1007/s00603-002-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Flaw Model to the Fracturing Around a Vertical Shaft

Abstract: SummaryThis paper investigates whether a micromechanical model developed to investigate the relation between the basic failure processes at grain-scale and the macroscopic failure pattern can be applied to model the fracturing around large-scale excavations. The simulated fracture pattern around a vertical shaft is compared to the fracturing around a shaft at a depth of 3400 m. The simulations suggest that wedge-shaped zones, called dog-ears, are formed by a progressive splitting-like failure of the rock. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Brittle rock is in nature a heterogeneous material which can be described by its internal microstructure. Micromechanical observations made during compression loading [ Hallbauer et al , 1973; Olsson and Peng , 1976; Kranz , 1983] have indicated that fracture initiation and fracture growth in brittle rock are to a large extent influenced by the presence of microstructure that introduces a heterogeneity in the stress distribution at the grain scale [ Van de Steen et al , 2003]. A key role of heterogeneity appears to be the creation of local concentrations of tensile stress, even when the rock as a whole is subjected only to compressive stress [ Gallagher et al , 1974; Blair and Cook , 1998a, 1998b].…”
Section: Introductionmentioning
confidence: 99%
“…Brittle rock is in nature a heterogeneous material which can be described by its internal microstructure. Micromechanical observations made during compression loading [ Hallbauer et al , 1973; Olsson and Peng , 1976; Kranz , 1983] have indicated that fracture initiation and fracture growth in brittle rock are to a large extent influenced by the presence of microstructure that introduces a heterogeneity in the stress distribution at the grain scale [ Van de Steen et al , 2003]. A key role of heterogeneity appears to be the creation of local concentrations of tensile stress, even when the rock as a whole is subjected only to compressive stress [ Gallagher et al , 1974; Blair and Cook , 1998a, 1998b].…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more discontinuum models are being used. They show that incorporating flaws or weaknesses in the model has an important effect on when fractures are induced around a circular opening, both at the laboratory scale (e.g., [38,48]) and in situ (e.g., [58]).…”
Section: Discussion: Consequences Of Results Obtainedmentioning
confidence: 99%
“…This statement clearly is supported by the numerous research projects that are still being conducted that focus on the basic type of loading applied in laboratory experiments. These projects often focus on a specific aspect, for example, the impact of heterogeneities (e.g., [10,27,28]), the orientations of flaws or weak planes (e.g., [21,[29][30][31]), and the characterisation of the (micro-)fracturing process by the analysis of acoustic emission signals (e.g., [15][16][17]32,33]). These are only a few of the many examples that use classic testing procedures.…”
Section: Discussionmentioning
confidence: 99%